2013
DOI: 10.1016/j.radonc.2012.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Proton therapy radiation pneumonitis local dose–response in esophagus cancer patients

Abstract: Purpose This study quantifies pulmonary radiation toxicity in patients who received proton therapy for esophagus cancer. Materials/methods We retrospectively studied 100 esophagus cancer patients treated with proton therapy. The linearity of the enhanced FDG uptake vs. proton dose was evaluated using the Akaike Information Criterion (AIC). Pneumonitis symptoms (RP) were assessed using the Common Toxicity Criteria for Adverse Events version 4.0 (CTCAEv4). The interaction of the imaging response with dosimetri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“…The authors reported that the highest prognostic value appeared with the lowest AIC value, which suggested that AIC can be a guideline in choosing a desired model. In a proton therapy research study [ 16 ], the AIC was used to determine the most appropriate model for the FDG uptake dose response for each patient. A compound-B based PET kinetic modeling study [ 17 ] used AIC to ensure a good kinetic parameter setting.…”
Section: Introductionmentioning
confidence: 99%
“…The authors reported that the highest prognostic value appeared with the lowest AIC value, which suggested that AIC can be a guideline in choosing a desired model. In a proton therapy research study [ 16 ], the AIC was used to determine the most appropriate model for the FDG uptake dose response for each patient. A compound-B based PET kinetic modeling study [ 17 ] used AIC to ensure a good kinetic parameter setting.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that FDG uptake can quantify normal tissue response in lung for patients with NSCLC and esophageal cancer (1520)]. Nijkamp et al also examined the use of posttreatment FDG-PET studies to quantify esophageal injury from radiation therapy (23).…”
Section: Discussionmentioning
confidence: 99%
“…Standard SUV Mean and SUV Max were not able to stratify or predict the progression of esophagitis. The choice of normalization has been utilized in studies of radiation-induced lung toxicity using FDG-PET (1520). Another study used change in FDG-PET SUV during radiation therapy relative to pre-treatment status (26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most (535/582, 92%) patients had adenocarcinoma and all underwent concurrent PBT, proton beam radiotherapy; CGE, cobalt gray equivalent; 5-FU, 5-fluorouracil; AP, anteroposterior; XRT, X-ray (photon) radiotherapy; LC, local control; DSS, disease-specific survival; OS, overall survival; DM, distant metastasis; IMRT, intensity-modulated radiotherapy; PA, posteroanterior; PFS, progression-free survival; RT, radiotherapy; GEJ, gastroesophageal junction; LPO, left posterior oblique; RPO, right posterior oblique; LRC, locoregional control; RFS, recurrence-free survival; DMFS, distant metastasis-free survival; 3DCRT, three-dimensional conformal radiotherapy; MS, median survival; LRR, locoregional recurrence; NS, nonsignificant. Table 1 lists several other articles examining PBT for esophageal cancers (9,(11)(12)(13)16,17). Over a decade of published PBT data point to the safety and efficacy of PBT for esophageal cancers, with or without chemotherapy and/or surgery.…”
Section: Esophagusmentioning
confidence: 99%